Beyond integration? : inter/disciplinary possibilities for the future of Christian higher education - Ream, Todd C.; Pattengale, Jerry A.; Riggs, David L. (David Lee), 1967- (Abilene Christian University Press, 2012)
The phrase "integration of faith and learning" has come to describe the way many Christian colleges and universities understand how all learning falls under the lordship of Jesus Christ. With its origins in the philosophical and theological insights of the Reformed tradition, this phrase has expanded its influence to institutions nurtured by numerous Christian traditions. This volume draws together prominent scholars who reflect on Christian higher education as it may exist beyond the integration model.